PENGARUH MOTIVASI BELAJAR DAN KREATIVITAS BELAJAR SISWA SMP TERHADAP HASIL BELAJAR IPA - Ni Made Lioni Garbriana .; Dra. Ni Ketut Rapi, M.Pd. .; Dra. Ni Made Pujani,M.Si . (Jurnal Pendidikan Fisika Undiksha, 2015)
Penelitian ini bertujuan (1) menganalisis pengaruh motivasi belajar terhadap hasil belajar IPA siswa kelas VII SMP Negeri Se-Kecamatan Banjar, (2) menganalisis pengaruh kreativitas belajar terhadap hasil belajar IPA siswa kelas VII SMP Negeri Se-Kecamatan Banjar, dan (3) menganalisis pengaruh motivasi belajar dan kreativitas belajar secara bersama-sama terhadap hasil belajar IPA siswa kelas VII SMP Negeri Se-Kecamatan Banjar. Jenis penelitian ini adalah ex-post facto korelasional. Populasi penelitian ini terdiri dari 1331 siswa kelas VII SMP Negeri Se-Kecamatan Banjar. Sampel penelitian diambil menggunakan teknik proporsional random sampling berjumlah 298 siswa. Data motivasi belajar dan data kreativitas belajar dikumpulkan dengan menggunakan kuesioner dengan masing-masing koefisien reliabilitas 0,82 dan 0,78. Data hasil belajar IPA diperoleh dengan menggunakan hasil tes yang mencakup materi “Besaran dan Satuan, serta Suhu dan Pengukurannya” dengan koefisien reliabilitas 0,84. Analisis data menggunakan teknik analisis deskriptif, teknik analisis regresi linier sederhana, dan regresi ganda dua prediktor. Hasil penelitian menunjukkan bahwa: (1) terdapat pengaruh positif motivasi belajar terhadap hasil belajar IPA siswa kelas VII SMP Negeri Se-Kecamatan Banjar (F = 8,928; p < 0,05) dan sumbangan efektif sebesar 1,43%; (2) terdapat pengaruh positif kreativitas belajar terhadap hasil belajar IPA siswa kelas VII SMP Negeri Se-Kecamatan Banjar (F = 9,962, p < 0,05) dan sumbangan efektif sebesar 2,07%, dan (3) terdapat pengaruh yang yang positif antara motivasi belajar dan kreativitas belajar secara bersama-sama terhadap hasil belajar IPA siswa di kelas VII SMP Negeri Se-Kecamatan Banjar (F = 5,373, p < 0,05) dan sumbangan efektif sebesar 3,5%. Kata Kunci : Motivasi Belajar, Kreativitas Belajar dan Hasil Belajar IPA. This study aimed at (1) analyzing the effect of learning motivation towards the science learning achievement of seventh grade students of all junior high schools in Banjar Sub-District, (2) analyzing the effect of learning creativity towards the science learning achievement of seventh grade students of all junior high schools in Banjar Sub-District, and (3) analyzing the effect of motivation and creativity in learning altogether toward the science learning achievement of seventh grade students of all junior high schools in Banjar Sub-District. This study was designed as co-relational ex-post facto. 1331 students of seventh grade of all junior high schools in Banjar Sub-District were the population of this study, and the sample taken by using proportional random sampling were 298 students. Data of students’ motivation and creativity in learning were obtained by using questionnaires in which the coefficient reliability of each questionnaire were 0.82 and 0.78. Data of students’ science learning achievement were obtained through the test which covered the material of “Quantities & Units”, and also “Temperature and its measurement” as well with the coefficient of reliability 0.84. Techniques used to analyze data were descriptive technique, simple linear regression technique, and double regression with two predictor technique. The results of this study shows that (1) there is a positive effect of learning motivation towards science learning achievement of seventh grade students of all junior high schools in Banjar Sub-District (F = 8.928; p < 0.05) and the effective contribution is 1.43%; (2) there is a positive effect of learning creativity in towards science learning achievement of seventh grade students of all junior high schools in Banjar Sub-District (F = 9.962, p < 0.05) and the effective contribution is 2.07%; (3) there is a positive effect between learning motivation and learning creativity altogether toward science learning achievement of seventh of all junior high schools in Banjar Sub-District (F = 5.373, p < 0.05) and the effective contribution was 3.5%. keyword : learning motivation, learning creativity, science learning achievement.